Beneficial effects of glycocholic acid (GCA) on gut mucosal damage in bile duct ligated rats - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 2001)
In order to investigate the effect of bile acids on gastrointestinal inflammations, bile duct ligated rats (BDL) were treated with GCA (25 mM/ml, oral or colonic) or saline 1 h before ethanol challenge and twice daily for 3 days in the ileitis group, while GCA was given twice daily for 3 days in the colitis group. BDL reduced the macroscopic and microscopic damage scores in the ileitis group compared to sham operated group, while it had no significant effect on ulcer or colitis groups. However, GCA given in BDL group reduced the ulcer index and microscopic damage in colitis group compared to saline-treated groups, but had no effect in ileitis group. Both BDL and GCA administration in BDL group reduced ileitis- or colitis-induced elevations in MPO levels. GCA administration in BDL group inhibited gastric acid output and volume. Our results suggest that oral or colonic administration of primary bile acids may be useful for the treatment of gastrointestinal inflammations.
Keywords: bile duct ligation; primary bile acids; ileitis; inflammatory bowel disease; ethanol injury; myeloperoxidase activity; INDUCED INTESTINAL LESIONS; ULCERATIVE-COLITIS; INDOMETHACIN; INFLAMMATION; DISEASE; BOWEL; PERMEABILITY; MARKER; MODEL